Nanosponge Drug Delivery System In Skin Care Medical Products: A Comprehensive Review - Priya Diwedi; Evneet Kaur Bhatia; Durgesh Kumari Gupta; Surya Prakash Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Recent advancements in nanotechnology have propelled nanosponge-based drug delivery systems to the forefront of skin care medical product development. These systems, composed of porous polymeric nanoparticles, offer controlled release and targeted delivery of therapeutic agents. They address challenges associated with conventional formulations, including skin irritation and poor patient compliance. Nanosponges efficiently encapsulate various active ingredients, enabling precise delivery to specific skin layers. They exhibit improved stability, prolonged action, and reduced side effects, making them promising for diverse dermatological conditions. This review discusses fabrication methods, characterization techniques, applications, and future prospects of nanospongebased drug delivery systems in skin care. Challenges and potential solutions in integrating nanosponges into skin care products are also addressed.